ETHICS OF KBIH SERVICE BASED ON ISLAMIC VALUES ININCREASING THE SATISFACTION OF THE HAJJ PILGRIMAGE - muhammad revan; arman solo harahap; Abdul Aziz Siregar; Muhlasin (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to examine the relationship between service ethics and pilgrim satisfaction through a conceptual synthesis that integrates service quality theory (SERVQUAL) with Islamic ethical principles. The approach used is qualitative with a literature review method of relevant national and international journals and academic books. The analysis was conducted using content analysis and thematic analysis based on the dimensions of reliability, responsiveness, assurance, empathy, and physical evidence, as well as the values of trustworthiness, ihsan, and social responsibility. The results of the study show that the satisfaction of Hajj pilgrims is multidimensional, covering functional, emotional, and spiritual aspects. Service quality integrated with Islamic ethical values has been proven to strengthen trust, increase positive perceptions, and shape a more meaningful worship experience. Service ethics is not only a complement but also the core of the religious service management system. This study produced a conceptual framework that emphasizes that the harmonization of technical competence and moral integrity of guides is a key factor in increasing pilgrim satisfaction. Theoretically, this study enriches the study of Islamic value-based service management, and practically provides strategic direction for a more holistic and congregation satisfaction-oriented management of KBIH services.